Hubungan antara Subjective Well-Being dengan Problematic Internet Use pada Mahasiswa - Putri, Nadhira Elza; Aulia, Farah (Lembaga Yasin AlSys, 2024)
The ever-growing internet can encourage students to experience the phenomenon of problematic internet use. This study aims to provide empirical evidence between the relationship between subjective well-being and problematic internet use in college students. This study is a correlational study of 272 students in West Sumatra. Data were collected using Diener's subjective well-being measurement tool and Caplan's generalized problematic internet use-2 (GPIUS2) which has been adapted into Indonesian. The sampling technique used was purposive sampling. Hypothesis testing using Spearman correlation showed a positive and significant relationship between subjective well-being and problematic internet use in students with r=0, 218 and a significant level of p=0.000 (p<0.05). The direction of the positive relationship means that the higher the subjective well-being, the higher the problematic internet use in students, on the other hand, the lower the subjective well-being, the lower the problematic internet use in students. These results indicate that students' high happiness is associated with strong Internet usage behavior, and the results of this study differ from previous studies.